2020
DOI: 10.21203/rs.3.rs-25064/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Analysis of the Biomechanical Behavior of two different design metaphyseal-fitting short stems using digital image correlation

Abstract: Background: The progressive evolution in hip replacement research is directed to follow the principles of bone and soft tissue sparing surgery. Regarding hip implants, a renewed interest has been raised towards short uncemented femoral implants. A heterogeneous group of short stems have been designed with the aim to approximate initial, post-implantation bone strain to the preoperative levels in order to minimize the effects of stress shielding. This study aims to investigate the biomechanical properties of tw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(58 reference statements)
1
0
0
Order By: Relevance
“…Amendola et al [29] reported similar findings in a series of 212 Tri-Lock BPS implanted hips. Furthermore, the results of the present study are in line with the conclusions of our previous experimental investigation [40], focused on the biomechanical behavior of the Tri-Lock BPS and Minima S femoral stem using digital image correlation. We demonstrated that stress shielding effect cannot be avoided since a proximal unloading of the femur was noted after the implantation of both short stem designs.…”
Section: Discussionsupporting
confidence: 91%
“…Amendola et al [29] reported similar findings in a series of 212 Tri-Lock BPS implanted hips. Furthermore, the results of the present study are in line with the conclusions of our previous experimental investigation [40], focused on the biomechanical behavior of the Tri-Lock BPS and Minima S femoral stem using digital image correlation. We demonstrated that stress shielding effect cannot be avoided since a proximal unloading of the femur was noted after the implantation of both short stem designs.…”
Section: Discussionsupporting
confidence: 91%